2012
DOI: 10.1111/jbi.12053
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal forest advance in northernmost Norway since the early 20th century

Abstract: Aim The arctic forest–tundra boundary is expected to advance rapidly northwards in response to climate warming. The purpose of this study was: (1) to analyse region‐wide changes in the positions of the latitudinal forest line and tree line since the early 20th century; (2) to calculate rates of northward movement and to estimate uncertainties from different sources of data; (3) to analyse how rates of advance differ between two common tree species, Betula pubescens (downy birch) and Pinus sylvestris (Scots pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 55 publications
3
84
0
1
Order By: Relevance
“…This is consistent with the advances of 3 to 11 m per year for the period of 1980-2000 in northern Russia [32], but it is much lower than the mean advance of 378 m per year (2.5 km from 2000 to 2009) reported for the pine forest line in northern Norway [77]. The variations observed for the Mealy Mountains study are attributed to site conditions, as seedling in the TTI in Labrador can be affected by the soil wetness, wind exposure, temperature [78], seedbed composition [79] and the topography [80].…”
Section: Discussionsupporting
confidence: 64%
“…This is consistent with the advances of 3 to 11 m per year for the period of 1980-2000 in northern Russia [32], but it is much lower than the mean advance of 378 m per year (2.5 km from 2000 to 2009) reported for the pine forest line in northern Norway [77]. The variations observed for the Mealy Mountains study are attributed to site conditions, as seedling in the TTI in Labrador can be affected by the soil wetness, wind exposure, temperature [78], seedbed composition [79] and the topography [80].…”
Section: Discussionsupporting
confidence: 64%
“…This warming coincides with increased woody shrub cover (Tape et al, 2006;Myers-Smith et al, 2015). The latitudinal treeline is also predicted to advance northward (Everett and Fitzharris, 1998;Pearson et al, 2013); however, observed rates of treeline advance have been slower than those predicted (Skre et al, 2002;Harsch et al, 2009;Hofgaard et al, 2013). In addition to warming, disturbance may be necessary to facilitate treeline advance by exposing new seedbeds, degrading shallow permafrost, and improving drainage, thereby creating opportunities for establishment in an ecosystem where recruitment is otherwise rare (Landhäusser and Wein, 1993;Lloyd et al, 2002;Chapin et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…According to a model presented by Paulsen and Körner [82], for example, treeline would be located at an elevation where the minimum length of the growing season is 94 days, with a daily minimum temperature just above zero (0.9 • C) and a mean of 6.4 • C during all these days. The extent of treeline advancement to greater elevations and more northerly latitudes, however, varies regionally, locally, and temporally as well as by tree species (e.g., [8,29,43,63,[83][84][85][86][87][88][89]). The direct influence of heat deficiency on tree establishment is often overruled by other abiotic and biotic factors (e.g., permanent strong winds and recurrent periods of drought).…”
Section: Treeline Dynamics At Different Spatial and Temporal Scalesmentioning
confidence: 99%
“…are of primary importance. Thus, the distance from the seed source, the way of seed dispersal (anemochoric, zoochoric), the overlying of seeds, the availability of viable seeds, seed predation, and the availability of favorable seed beds (e.g., [5,85,87,88,[90][91][92][93]) are relevant factors that need further examination. However, discussion of whether reduced availability of viable seeds are playing a major role or not is controversial (e.g., [3,5,17,19,45,87,90,[93][94][95][96][97]).…”
Section: Treeline Dynamics At Different Spatial and Temporal Scalesmentioning
confidence: 99%